Enhancement of tetravalent immune responses to highly conserved epitopes of a dengue peptide vaccine conjugated to polystyrene nanoparticles - Chan, Yanqi; Jazayeri, S. D. *; Ramanathan, Babu *; Poh, Chit Laa * (MDPI, 2020)
Vaccination remains the major approach to the prevention of dengue. Since the only licensed live attenuated vaccine (LAV) lacked eﬃcacy against all four serotypes, other vaccine platforms, such as synthetic peptide vaccines, should be explored. In this study, four multi-epitope peptides (P1–P4)were designed by linking a universal T-helper epitope (PADREorTpD) to the highly conserved CD8 T cell epitope and B cell epitope (B1 or B2) against all four DENV serotypes. The multi-epitope peptides were conjugated to polystyrene nanoparticles (PSNPs) and four nanovaccines (NP1–NP4) were constructed. Mice immunized with NP1–NP4 elicited signiﬁcantly higher titers of IgG and neutralizing antibodies when compared to immunization with naked P1–P4. The immune responses in mice immunized with peptide vaccines were compared with nanovaccines using ELISA, ELISPOT, and a neutralization test based on FRNT50. Among the four conjugated peptide nanovaccines, NP3comprisingtheTpDT-helper epitope linked to the highly conserved B1 epitope derived from the E protein was able to elicit signiﬁcant levels of IFN-γ and neutralizing antibodies to all four dengue serotypes. NP3 is a promising tetravalent synthetic peptide vaccine, but the selection of a more eﬀective CD8+ T cell epitope and adjuvants to further improve the immunogenicity is warranted.